Perancangan Homestay Moni Kecamatan Kelimutu Kabupaten Ende (Tema Arsitektur Neo Vernakuler) - Babo, Dominggus Piterson; Mochdar, Dian Fitriawati; Kerong, Fabiola T. A. (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2024)
ABSTRACT DOMINGGUS PITERSON BABO 2018320320. Moni Homestay Design, Kelimutu District, Ende Regency (Neo Vernacular Architecture Theme). Faculty of Engineering, University of Flores, Ende, 2023.. Mobile Number : 081339344579, E-mail : babosoni@gmail.com supervisor I : Ir. Dian Fitriawati Mochdar, ST., MT. supervisor II : Fabiola T.A, Kerong. ST., MT. Moni Kelimutu tourist destinations include culinary tourism, shopping tourism, and recreational tourism. This has a positive impact because the number of tourists coming is increasing. Therefore Homestay lodging is a very important element to support the existing potential. Homestay has an important role to introduce the character of each region. Ende Regency is one of the districts with many tribes and precisely in the Kelimutu sub-district, the local community highly respects customs and habits, so Moni's homestay is designed with the Neo Vernacular theme which aims to strengthen the identity and character of the local indigenous tribes. The application of this theme is dominated by wood elements as an aesthetic element of the building both in the facade of the building and in the atmosphere of the building space. Wood is the main material for building traditional Lio houses. So that the Homestay is designed to have the feel of the local environment so that people who stay at this Homestay feel the character of the local area. The methods used in this planning and design are 1). data collection methods include primary data (observation, documentation and interviews) and secondary data (literature studies and comparative studies); 2). The analysis method explains each analysis which contains field data, design criteria (theory), alternative analysis (alternative 1 and alternative 2), and responses (alternative selection). Analysis methods include analysis of design objects; site analysis; functional analysis (space organization, namely the organizational structure of actors, analysis of activities and space requirements (analysis of actors and actors' activities), room analysis (conditions, circulation, organization, relationships, size and zoning of space), shape analysis and analysis of building mass placement patterns; analysis building systems (structure and utilities); as well as analysis of regional regulations. 3). The design method includes design ideas and design concepts, namely the concept of neo vernacular architecture. The results obtained from designing Moni's homestay are based on a neo vernacular architectural approach which emphasizes more on building materials and site processing. The facilities built include the main facilities in the form of accommodation (suite room and standard type homestay), management building, as well as supporting facilities in the form of a cafeteria, photo spot, outdoor room and service area, parking. Keywords: Tourism, Homestay, Neo Vernacular Architecture